Synthesis of nanostructured block copolymer in supercritical carbon dioxide - Alauhdin, Mohammad (2017)
This thesis aims to expand our knowledge of block copolymer synthesis, particularly in supercritical CO2 (scCO2) and to study the microphase separation behaviour occurring within block copolymer microparticles during the synthesis. For these purposes, a new synthesis strategy was proposed and a high pressure X-ray autoclave was built and tested to facilitate the in situ microphase separation investigation by X-ray scattering. The success of this project has significantly broaden our understanding of the block copolymer synthesis and its phase separation mechanism in scCO2 dispersion, which are highly important to generate self-organised nanostructures. For the synthesis of block copolymers, a two-stage method has been successfully applied to add flexibility to the existing synthesis method, by allowing each block to be synthesised in independent steps. The results indicated that this method can be used for synthesising a variety of poly(methyl methacrylate)-based block copolymers. Importantly, these block copolymers can be prepared in a much shorter timeframe, since the polymerisation of the second block can be decoupled from the first. Different internal morphologies of the block copolymers were observed, including body centred cubic packing of spheres (SPH), hexagonally packed cylinders (CYL), bicontinuous gyroid (GYR), and lamellae (LAM). These morphologies were obtained by changing either the block copolymer pairs or the block volume fractions. A new design of high pressure X-ray autoclave has been constructed and successfully applied in the monitoring of time-resolved Small-Angle X-ray Scattering (SAXS) during the Reversible Addition-Fragmentation Chain Transfer (RAFT) dispersion polymerisation in scCO2 using synchrotron radiation. During polymerisation of styrene using PMMA macro-RAFT agent, the microphase separation of PMMA-b-PS block copolymers developed with reaction time resulted in more distinct domains and an increase in the domain spacing. The investigation revealed that the nanostructured morphologies remain invariant from the initial formation. However, the ordering of the nanostructures was found as the polymerisation proceed. We then sought to expand the potential of the two-stage synthesis method for preparing polymer/metal nanoparticle hybrid materials. Nanostructured PMMA-b-PDMAEMA block copolymer was selected as the host polymer. In this approach, the second block, PDMAEMA, can be synthesised while generating silver nanoparticles (AgNPs) in one-pot process. Importantly, the AgNPs can be located in the PDMAEMA domain selectively since the tertiary amine groups of the growing PDMAEMA chains anchored the AgNPs. This synthesis method produces a clean material as the solvent is readily removed on depressurisation and there was no additional reducing agent.